Sensitivity of the Absorbance and Capacitance Methods in Measurement the Number of Cells In-vivo - Musaddiq Musbach (Indonesian Association of Physicists in Medicine (AIPM/AFISMI), 2015)
Have been carried out measurement of the number of cells in vivo by using two methods, namely measuring the absorbance using spectrophotometer and the capacitance of the liquid capacitor is designed himself. The results of both experiments suggests that the capacitance method is more sensitive and transparent than the absorbance method at once proves that it could only be used for a limited range of cell numbers. In contrast, the capacitance method could be used for more wider range of cell numbers.